(untitled) (Acta Scientiarum. Agronomy, 2011)
The cotton production system in Brazil concentrates on the area of the cerrado, characterized by frequent rains that interfere in the effectiveness of the necessary sprays during its cycle. The objective of the work was to evaluate simulate rain of 15 mm in 4 hours after spraying in the control of Aphis gossypii with insecticide flonicamid. Plants of Gossypium hirsutum were cultivated in pots containing soil as substrate in greenhouse conditions. The pots were arranged in randomized complete design with seven treatments and five replicates, consisting of: test without insecticide spraying, without insecticide spraying with rain, flonicamid spraying with simulate rain of 15 mm after 30 minutes, 1, 2 and 4 hours after spraying. Equivalent insecticide was sprayed 75 g of flonicamid by hectare. The efficiency evaluation was accomplished through the individuals of A. gossypii count which started from an artificial infestation 6 days before the application of the treatments. The results were: a 15-mm precipitation during the first four hours after flonicamid spraying interfered negatively in the control of A. gossypii.